The implications of ghubn in islamic contracts : an analysis of current practices - Omar, Muhammad Naim; Arifin, Mahamad; Mohammad Napiah, Mohammad Deen; Abdullah, Mohamad Asmadi (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Mutual consent is one of the important elements in Islamic law of contracts. However, the consent itself may be disrupted by defects that can affect parties to the ontracts. There are a number of vitiating factors that may have effect on the validity of contract such as tadlis, ikrah, ghubn etc. This article however seeks only to focus on the concept of ghubn and its effects on contracts. In doing so, the study will look into the meaning of ghubn, its classification as well as its effect on the consent of contracting parties. Juristic views of renowned school of Islamic laws will be consulted. On the issue of temporary practices, there are types of contract whereby, one of the contracting parties has no choice, but to agree to the prices as stipulated in terms and conditions imposed by the other party. In this case, even though the contracts are considered as legally valid by the presence of offer and acceptance (‘aqd), the question may arise whether what appears in the contracts really reflects the actual consents of the parties This issue will also be discussed in this paper, together with a few other related concepts, such as, talaqqi al-rukban, najash, khiyar ,mustarsil etc. It is found that in general, any party affected by ghubn may seek remedy through khiyar al-ghubn. In order to invoke this type of khiyar certain conditions must be fulfilled inter alia, the contracting party is ignorant of the market price and the ghubn is excessive.